Strain self-sensing tailoring in functionalised carbon nanotubes/epoxy nanocomposites in response to electrical resistance change measurement - An, Donglan; Nourry, Jim; Gharavian, Somayeh; Thakur, Vijay Kumar; Aria, Adrianus Indrat; Durazo-Cardenas, Isidro; Khaleque, Tasnuva; Nezhad, Hamed Yazdani (SSRN, 2020)
Carbon nanotubes (CNTs) are inherently multifunctional, conductive and possess piezo-resistive characteristics. Aiming at the multi-functionality of materials, nanocomposites made of epoxy resin with embedded CNTs are a promising solution for strain self-sensing applications. A critical parameter to achieve repeatable and reliable measure is the CNTs dispersion state in the resin. This study investigated the effect of CNTs concentration (0.01 wt% and 0.1 wt%), with different loading of surfactant Triton X-100, (0.0%, 0.2%, 0.5% and 1.0%) on strain sensing in terms of sensitivity and linearity based on electrical resistance data. The CNTs were synthesised directly using an injection floating catalyst chemical vapor deposition (ICCVD) process and their quality was characterised by Raman spectroscopy and scanning electron microscopy. Only the epoxy modified with 0.1 wt% CNTs exhibited sufficient piezo-resistivity for the resistance measurements, and those with 0.01 wt% CNTs did not show sufficiently measurable conductivity so were excluded in our study, since their CNTs were highly entangled, and conductive network failed to be established. It was observed that, with 0.1 wt% CNTs, adding 0.5% content of the surfactant improved gauge factor. With more content of the surfactant (1.0 %), surprisingly, we observed a drop of gauge factor by the order of two. Therefore, by comparing the conductivity change between 1.0% and 0.5% surfactant, we postulated that the relatively high content surfactant has reached critical micelle concentration, and negatively affects CNTs dispersion state. The research presented in this article shows that moderate content of surfactant could improve piezo-resistivity gauge factor while excessive surfactant could cause adverse effect.
Keywords: surfactant; in-situ strain measurement; self-sensing; piezo-resistivity; nanocomposites; Carbon nanotubes